2017
DOI: 10.5414/np300980
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic spread of systemic neoplasms to central nervous system tumors: review of the literature and case presentation of esophageal carcinoma metastatic to meningioma

Abstract: Metastatic spread of a systemic neoplasm to a central nervous system malignancy is a rare but well-documented phenomenon. Over 100 case reports of tumor-to-tumor spread involving the central nervous system have been described since the first report in 1930. Overwhelmingly, intracranial meningioma represents the most common recipient tumor, while breast and lung are the first and second most common donor malignancies, respectively. The propensity for meningiomas to harbor metastatic lesions has been attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…There are several criteria to diagnose TTM and differentiate it from a collision tumor ( Tables 1 and 2 ) [ 8 9 ]. According to Campbell et al [ 8 ], TTM can be diagnosed when the following conditions are satisfied: 1) coexistence of two or more primary tumors; 2) the host tumor must be a true neoplasm; 3) histologically different tumor tissue must enclose the metastatic focus, not be of contiguous growth, with the absence of an intermediate transitional zone; and 4) extravascular metastasis must be present with the exclusion of metastasis to the lymphatic system (such as lymphoma) where the second primary tumor is present with an active hematologic malignancy ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several criteria to diagnose TTM and differentiate it from a collision tumor ( Tables 1 and 2 ) [ 8 9 ]. According to Campbell et al [ 8 ], TTM can be diagnosed when the following conditions are satisfied: 1) coexistence of two or more primary tumors; 2) the host tumor must be a true neoplasm; 3) histologically different tumor tissue must enclose the metastatic focus, not be of contiguous growth, with the absence of an intermediate transitional zone; and 4) extravascular metastasis must be present with the exclusion of metastasis to the lymphatic system (such as lymphoma) where the second primary tumor is present with an active hematologic malignancy ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 Research has also suggested that high vascularity and locations of recipient sites play a role in the process of a metastasis situating itself within another tumour. 3 This is known as the “mechanical theory”.…”
Section: Discussionmentioning
confidence: 99%
“…2 , 10 , 11) The majority of metastases arise from lung or breast carcinomas. 10 , 12 , 13) Other types of benign intracranial tumors, such as schwannoma and pituitary adenoma, have rarely been reported. 12) Contrastingly, RCC-to-hemangioblastoma is the most common donor–recipient tumor association among tumor-to-tumor metastasis cases.…”
Section: Discussionmentioning
confidence: 99%